Chronic Kidney Dysfunction Can Increase the Risk of Deep Vein Thrombosis after Total Hip and Knee Arthroplasty - Li, Qiangqiang (Biomed Res Int, 2017)
BACKGROUND: Deep vein thrombosis (DVT) is one of the major complications of total joint arthroplasty (TJA). Chronic kidney dysfunction (CKD) has proven to promote a proinflammatory and prothrombotic state and is prevalent among patients undergoing TJA. The purpose of this study is to identify whether CKD increase the risk of DVT following TJA. METHODS: In a retrospective study, 1274 patients who underwent primary TJA were studied. CKD is graded in 5 stages. Univariate and multivariate analysis were used to identify the association of CKD and its severity with postoperative DVT. RESULTS: There were 1139 (89.4%) participants with normal kidney function, 103 (8.1%) with mildly decreased kidney function, and 32 (2.5%) with stage 3 and 4 CKD. A total of 244 patients (19.2%) were diagnosed with DVT. Sixty-four patients (5.0%) developed symptomatic DVT. Advanced age, female gender, malignancy, and eGFR showed significant association with total DVT. BMI, thrombosis history, malignancy, and eGFR were associated with symptomatic DVT. After adjusting for age, gender, BMI, and malignancy, eGFR was found to be related to both total and symptomatic DVT. CONCLUSIONS: CKD is an important risk factor for both total and symptomatic DVT following TJA. Postoperative prophylaxis should be made a priority in this population.